REMAINING INFLAMMATORY KIDNEY DISEASE - CREATIONS OF THE CLINIKAL PICTURE - Khayrilloeva Mekhribon Xurshedovna; Vafoeva Nigora Abrorovna (Journals Park Publishing, 2024)
Pyelonephritis in woman is the most communal kidney sickness in all age groups. A higher occurrence of pyelonephritis in girls and woman is owing to the anatomical and physiological physiognomies of the female figure. The from top to bottom incidence of long-lasting pyelonephritis, its exacerbation, difficulties in woman reproduction age touch their general prevalence, lifetime prospect and generative meaning. A polymorphic picture characterizes urinary sediment in woman with pyelonephritis. An upsurge in the equal of cretinin in the blood is renowned.
Keywords: chronic pyelonephritis, pyelocaliceal system, kidney injury, creatinine.